The influence of culture and transparency on global research and development intensity: an overview across Europe - Lopes, I. T.; Serrasqueiro, R. M. (Contaduría y Administración, 2017)
Culture and transparency can be broadly described as a set of beliefs, norms, and actions, which drive the human action into innovativeness and, over the centuries, have driven individuals, groups, organizations, and nations, into the most complex networking schemes. It seems unquestionable that those beliefs and policies, affect both private and public organizations, driving them across innovation wages in a more incremental or radical way. This research aims to explore the impact of culture and transparency on R&D attractiveness in public and business enterprise sectors. Using information from 31 European countries over the period 2010-2014, total R&D expenditures were regressed against several variables such as the Hofstede’s cultural dimensions, the Public Sector Transparency Index, and other macroeconomic aggregated variables. Most of the theoretical assumptions are significantly supported by the empirical outcomes. Thus, only proactive and minded set based economies, oriented to efficient knowledge transformation mechanisms, can support high private and public R&D expenditures efforts through some innovative based dynamics.